Revisit of Reconstituted 30-nm Nucleosome Arrays Reveals an Ensemble of Dynamic Structures. Issue 18 (14th September 2018) - Zhou, Bing-Rui; Jiang, Jiansheng; Ghirlando, Rodolfo; Norouzi, Davood; Sathish Yadav, K.N.; Feng, Hanqiao; Wang, Rui; Zhang, Ping; Zhurkin, Victor; Bai, Yawen
Abstract: It has long been suggested that chromatin may form a fiber with a diameter of 30 nm that suppresses transcription. Despite nearly four decades of study, the structural nature of the 30-nm chromatin fiber and conclusive evidence of its existence in vivo remain elusive. The key support for the existence of specific 30-nm chromatin fiber structures is based on the determination of the structures of reconstituted nucleosome arrays using X-ray crystallography and single-particle cryo-electron microscopy coupled with glutaraldehyde chemical cross-linking. Here we report the characterization of these nucleosome arrays in solution using analytical ultracentrifugation, NMR, and small-angle X-ray scattering. We found that the physical properties of these nucleosome arrays in solution are not consistent with formation of just a few discrete structures of nucleosome arrays. In addition, we obtained a crystal of the nucleosome in complex with the globular domain of linker histone H5 that shows a new form of nucleosome packing and suggests a plausible alternative compact conformation for nucleosome arrays. Taken together, our results challenge the key evidence for the existence of a limited number of structures of reconstituted nucleosome arrays in solution by revealing that the reconstituted nucleosome arrays are actually best described as an ensemble of various conformations with a zigzagged arrangement of nucleosomes. Our finding has implications for understanding the structure and function of chromatin in vivo . Graphical Abstract: Unlabelled Image Highlights: Disulfide cross-linking can alter nucleosome array conformation population. Crystal packing conduces tetra-nucleosome array compaction. Glutaraldehyde cross-linking can perturb nucleosome array conformation. A novel ladder-like nucleosome packing mode Thirty-nanometer nucleosome arrays exist as an ensemble of dynamic structures.